DERADIKALISASI PENAFSIRAN AL-QUR’AN - Arifin, Mohammad Zaenal (EMPIRISMA: JURNAL PEMIKIRAN DAN KEBUDAYAAN ISLAM, 2015)
Tafsir is an attempt to understand the Qur’an from all its aspects according to the human capacity. The products of tafsir certainly plays a significant role in determining how public will understand Islam. Therefore, a Qur’anic interpretation should be built upon a noble goal, which is to provide an ontological view that the Qur’an is a “Book of Raḥmah” encouraging the people to create a tolerant and moderate society. This paper is an attempt to break the chain that led to the emergence of reconstructing radical interpretation of the Qur’an. It will first present a critique on those radical interpretations, and then reconstruct them within the framework of the Qur’an’s ṣāliḥ li kulli zamān wa makān.Keywords: Radikalisasi, Deradikalisasi, ṣāliḥ li kulli zamān wa makān